Donor specific HLA antibody in hematopoietic stem cell transplantation: Implications for donor selection - Krummey, Scott M.; Gareau, Alison J. (Frontiers in Immunology, 2022)
Advances in hematopoietic stem cell transplant (HSCT) have led to changes in the approach to donor selection. Many of these new approaches result in greater HLA loci mismatching, either through the selection of haploidentical donors or permissive HLA mismatches. Although these approaches increase the potential of transplant for many patients by expanding the number of acceptable donor HLA genotypes, they add the potential barrier of donor-specific HLA antibodies (DSA). DSA presents a unique challenge in HSCT, as it can limit engraftment and lead to graft failure. However, transient reduction of HLA antibodies through desensitization treatments can limit the risk of graft failure and facilitate engraftment. Thus, the consideration of DSA in donor selection and the management of DSA prior to transplant are playing an increasingly important role in HSCT. In this review, we will discuss studies addressing the role of HLA antibodies in HSCT, the reported impact of desensitization on DSA levels, and the implications for selecting donors for patients with DSA. We found that there is a clear consensus that moderate strength DSA should be avoided, while desensitization strategies are reported to be effective in most cases at reducing DSA to amenable levels. There is limited information regarding the impact of specific characteristics of DSA, such as HLA loci or overall level of sensitization, which could further aid in donor selection for sensitized HSCT candidates.